Peran Keluarga Muda Jawa terhadap Penggunaan Bahasa Jawa pada Ranah Keluarga di Lingkungan Perkampungan Kota Semarang - Suryadi, M (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The research aims is to determine the strength and the role of families, especially the families of the village who were used Javanese Language. Nowadays, the Javanese language the developed is the reflection of family concern, especially the role of parents in inheriting the use of Javanese Language (normative-prescriptive). The research location is in Semarang City. The method that used to obtain data was the method refer to: observation, record, and method of proficient: participant, interviews. Data analysis used descriptive-quantitative method, i.e. Ervin-Tripp alternation rule (1972). The result of this research that the role of family is very influential on the mastery and use of Javanese Language, as well as coloring the Javanese Language on the present-day. The family has three main roles, namely (1) the gateway to the introduction of the Javanese Language, (2) the gateway to learning Javanese Language, and (3) the gateway to preservation of Javanese.